Regulasi Financial Fair Play (FFP) sebagai Rezim Pencegah Praktik Money laundering dalam Industri Sepak Bola Eropa - Dimas Feriyanto; Ika Riswanti Putranti; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Football is one of the most popular sports in the world, especially in Europe. The popularity of European football cannot be separated from its increasing industrial development, with large of money flows in it. The large money flows has a vulnerability to crimes in the financial sector, especially money laundering. Therefore, this study will reveal how the vulnerability of the football industry to money laundering practices and how the role of Financial Fair Play (FFP) regulations on preventing these practices from occurring in the European football industry. Data was collected using the literature study method from various scientific journals, news, and official The Union of European Football Associations (UEFA) archives, and then analyzed using the congruent method. This study shows that the practice of money laundering is vulnerable to occur through the structural, financial, and cultural sectors in the football industry. Then through its role as an international regime with several regulations such as break-even, club ownership, and the role of the Club Financial Control Body (CFCB), Financial Fair Play (FFP) regulations can indirectly reduce some of the vulnerabilities of money laundering practices in the European football industry.